Sleep hygiene intervention for youth aged 10 to 18 years with problematic sleep: a before-after pilot study - Tan Evan; Healey Dione; Gray Andrew R; Galland Barbara C (BMC, 2012)
Abstract Background The current study aimed to examine the changes following a sleep hygiene intervention on sleep hygiene practices, sleep quality, and daytime symptoms in youth. Methods Participants aged 10-18 years with self-identified sleep problems completed our age-appropriate F.E.R.R.E.T (an acronym for the categories of Food, Emotions, Routine, Restrict, Environment and Timing) sleep hygiene programme; each category has three simple rules to encourage good sleep. Participants (and parents as appropriate) completed the Adolescent Sleep Hygiene Scale (ASHS), Pittsburgh Sleep Quality Index (PSQI), Sleep Disturbance Scale for Children (SDSC), Pediatric Daytime Sleepiness Scale (PDSS), and wore Actical® monitors twice before (1 and 2 weeks) and three times after (6, 12 and 20 weeks) the intervention. Anthropometric data were collected two weeks before and 20 weeks post-intervention. Results Thirty-three youths (mean age 12.9 years; M/F = 0.8) enrolled, and retention was 100%. ASHS scores significantly improved (p = 0.005) from a baseline mean (SD) of 4.70 (0.41) to 4.95 (0.31) post-intervention, as did PSQI scores [7.47 (2.43) to 4.47 (2.37); p < 0.001] and SDSC scores [53.4 (9.0) to 39.2 (9.2); p < 0.001]. PDSS scores improved from a baseline of 16.5 (6.0) to 11.3 (6.0) post- intervention (p < 0.001). BMI z-scores with a baseline of 0.79 (1.18) decreased significantly (p = 0.001) post-intervention to 0.66 (1.19). Despite these improvements, sleep duration as estimated by Actical accelerometry did not change. There was however a significant decrease in daytime sedentary/light energy expenditure. Conclusions Our findings suggest the F.E.R.R.E.T sleep hygiene education programme might be effective in improving sleep in children and adolescents. However because this was a before and after study and a pilot study with several limitations, the findings need to be addressed with caution, and would need to be replicated within a randomised controlled trial to prove efficacy. Trial registration Australian New Zealand Clinical Trials Registry: ACTRN12612000649819